Pengaruh Model Pbl (Problem Based Learning) Terhadap Motivasi Dan Hasil Belajar Ipa - Purwanto, Farich; Santoso, Khairun Nisa’ (Universitas Islam Zainul Hasan Genggong, 2023)
This study aims to determine the effect of the PBL (Project Based Learning) model on student motivation and learning outcomes, where the research was at SDI M. Ishak Bin Ramzan Kraksaan Probolinggo. This type of research is a quasi-experimental design with pretest-posttest nonequivalent control group design. The study population was students of SDI M. Ishak Bin Ramzan Kraksaan Probolinggo which consisted of seven classes with a total of 86 students. The research sample was selected by double random sampling technique, one experimental class and one control class. Data collection uses a questionnaire instrument to measure learning motivation and learning achievement test instruments to measure student learning outcomes. Research data were analyzed using descriptive and inferential statistical analysis techniques. The average score of motivation after learning is 105.6 (high category) and the average value of learning outcomes is 87.17 (very high category). The results of inferential analysis using the t-test of learning motivation obtained a tcount of 1.89 and the results of the t-test of learning outcomes tcount of 4.57. Both of these results show that tcount > ttable (ttable 1.67). This means that H0 is rejected and H1 is accepted. It can be concluded that there is an influence of the PBL model on the motivation and learning outcomes of students in class V SDI M. Ishak Bin Ramzan Kraksaan Probolinggo on the subject matter of objects and their properties.